2014
DOI: 10.1093/comnet/cnu034
|View full text |Cite
|
Sign up to set email alerts
|

Generating online social networks based on socio-demographic attributes

Abstract: Recent years have seen tremendous growth of many online social networks such as Facebook, LinkedIn and MySpace. People connect to each other through these networks forming large social communities providing researchers rich datasets to understand, model and predict social interactions and behaviors. New contacts in these networks can be formed due to an individual's demographic attributes such as age group, gender, geographic location, or due to a network's structural dynamics such as triadic closure and prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…If the social graph was generated only based on a known node-number distribution, we would get a fairly homogeneous network without some characteristic features of empirical social networks. Many studies have focused specifically towards the creation of a model for generating social graphs [11]- [15], [24], [30], [31]. The shared goal between them is to generate a synthetic social graph that has characteristics similar to an empirical social graph, but using different approaches.…”
Section: Synthetic Datasets Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…If the social graph was generated only based on a known node-number distribution, we would get a fairly homogeneous network without some characteristic features of empirical social networks. Many studies have focused specifically towards the creation of a model for generating social graphs [11]- [15], [24], [30], [31]. The shared goal between them is to generate a synthetic social graph that has characteristics similar to an empirical social graph, but using different approaches.…”
Section: Synthetic Datasets Generationmentioning
confidence: 99%
“…the number of nodes. Then, using some of the existing approaches [11]- [15], [24], [30], [31], [57] we can generate the binary friendship graph of the selected size. Siddula et al [29] suggest the Small World Topology algorithm [12] as a very good representation of OSN binary social graph, thus we recommend using this algorithm for generating a binary friendship graph.…”
Section: Conceptual Solution For Generating Synthetic Expanded Social Graphmentioning
confidence: 99%
See 1 more Smart Citation
“…As a special case, for a fixed k, consider the list L(k) consisting of all pairs of unconnected vertices u and such that d(u, ) = k. A network may have many such pairs. It is known that compared to the pairs of unconnected vertices that have distance k + 1, members of L(k) are more likely to form a link during the test interval [17,58]. However, the question remaining open is what elements of L(k) are more likely to be connected than the other members?…”
Section: Link Predictionmentioning
confidence: 99%
“…Holme & Kim (2002) proposed a way how to complement preferential attachment models with triad formation which generates networks with both scale-free and small world properties. Pasta, Zaidi, & Rozenblat (2014) added principles how to involve demographic properties to such networks. And Li et al (2014) showed how it is possible to artificially build social networks which are sparse/dense and assortative/dissassortative and where these properties my change over the social network evolution.…”
Section: Modelling Diffusion Of Information In Online Social Media Usmentioning
confidence: 99%